Sino-Russian “energy marriage”: evidence of cooperation from the belt and road initiative - Sh. Feng; J. Wang; F. Wang (Сравнительная политика, 2023)
Energy plays a vital role as the lifeblood of economic development, and China’s rapid economic growth necessitates a stable and secure energy supply. In this context, energy trade between China and Russia, under the framework of the of the One Belt One Road initiative, becomes a crucial element of China’s energy strategies. This paper employs a combination of quantitative and qualitative methods to comprehensively analyze the historical, current, and future aspects of energy cooperation between the two nations. Amidst the current international landscape, the energy cooperation structures of China and Russia exhibit complementarity, rendering the energy collaboration between both countries mutually beneficial. Hence, it is essential for China and Russia to reinforce their energy cooperation further, paving the way for a prosperous and symbiotic relationship in the energy sector.